Herbicide and crop rotation effects on the weed complex - Doll, Jerry D.; Piedrahíta Castañeda, Wilson (International Center for Tropical Agriculture, 1981)
A four-season trial was conducted using continuous maize (Zea mays L.) and soybeans (Glicine max (L.) Merr.) with the continuous use, rotation or combination of various herbicides to determine weed species shifts. No weed species increased in maize treated for four seasons with atrazine (2-chloro-4-(Etylamino)-6(Isopropylamino)-2-triazine) or the combination atrazine + alachlor (2-chloro-2`, 6` -diethyl-N-(methoxy-methyl)acetanilide). Four seasons of alachlor allowed a 6 and 21 percent increase in broadleaf weeds in maize and soybeans, respectively, while maintaining excellent grass weed control. In soybeans a 21 percent increase in broadleaf weeds occurred after four seasons of linuron (3-(3,4-dichlorophenyl)-1-methoxy-1-methylurea). Linuron combined with alachlor gave the best weed control in soybeans while the rotation of herbicides was less effective. In both crops, two hand weedings for four seasons tended to reduce the weed population the following year